Biotic pump of atmospheric moisture as driver of the hydrological cycle on land - Makarieva, A. M.; Gorshkov, V. G. (CCSD, 2007)
International audience In this paper the basic geophysical and ecological principles are jointly analyzed that allow the landmasses of Earth to remain moistened sufficiently for terrestrial life to be possible. 1. Under gravity, land inevitably loses water to the ocean. To keep land moistened, the gravitational water runoff must be continuously compensated by the atmospheric ocean-to-land moisture transport. Using data for five terrestrial transects of the International Geosphere Biosphere Program we show that the mean distance to which air fluxes can transport moisture over non-forested areas, does not exceed several hundred kilometers; precipitation decreases exponentially with distance from the ocean. 2. In contrast, precipitation over extensive natural forests does not depend on the distance from the ocean along several thousand kilometers, as illustrated for the Amazon and Yenisey river basins and Equatorial Africa. This points to the existence of an active biotic pump transporting atmospheric moisture inland from the ocean. 3. Physical principles of the biotic moisture pump are investigated based on the previously unstudied properties of atmospheric water vapor, which can be either in or out of aerostatic equilibrium depending on the lapse rate of air temperature. A novel physical principle is formulated according to which the low-level air moves from areas with weak evaporation to areas with more intensive evaporation. Due to the high leaf area index, natural forests maintain high evaporation fluxes, which support the ascending air motion over the forest and "suck in" moist air from the ocean, which is the essence of the biotic pump of atmospheric moisture. In the result, the gravitational runoff water losses from the optimally moistened forest soil can be fully compensated by the biotically enhanced precipitation at any distance from the ocean. 4. It is discussed how a continent-scale biotic water pump mechanism could be produced by natural selection acting on individual trees. 5. Replacement of the ...